Effectiveness and Accountability of Zakat Fund Management at LAZ Yakesma Based on the Analysis of Sharia Financial Ratios 2017-2022 - Ummah, Syarifatul; Yusuf, Sri Dewi; Kadir, Rifadli D.; Sekarrini, Laras Ayu (Manunggal Halim Jaya, 2025)
This study aims to analyze the effectiveness of Islamic social institutions through a case study on the Madani Welfare Foundation (Yakesma), utilizing six ratios as a measure. This study uses a descriptive quantitative approach to calculate each effectiveness ratio. Data was collected through Yakesma's financial statement documentation for six years, namely 2017-2022. The analysis was conducted by calculating the effectiveness ratio, which comprised the distribution ratio, ZIS fund growth, distribution growth, amil rights to collection, the use of amil funds to fulfill amil rights, and the allocation of funds to poor people for zakat distribution. The results of this ratio calculation are then integrated with the four pillars of Islamic Economics, namely transparency, accountability, efficiency, and Sharia compliance. Based on the analysis results, it was found that Yakesma successfully maintained a high and consistent distribution ratio (>77%), demonstrating its effectiveness in distributing ZIS to the mustahik. Additionally, the trend of growth and fund disbursement demonstrated a positive performance. Yakesma demonstrates a good level of accountability through independent audits and the publication of financial statements. These findings suggest that other Islamic social institutions can adopt the practices of financial report transparency, amil fund management discipline, and accountable governance, as applied by Yakesma, to increase public trust, muzakki participation, and optimize benefits for the mustahik.